2010
DOI: 10.1099/mic.0.037796-0
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific recognition of pyochelin and enantio-pyochelin by the PchR proteins in fluorescent pseudomonads

Abstract: The siderophore pyochelin of Pseudomonas aeruginosa promotes growth under iron limitation and induces the expression of its biosynthesis genes via the transcriptional AraC/XylS-type regulator PchR. Pseudomonas fluorescens strain CHA0 makes the optical antipode of pyochelin termed enantio-pyochelin, which also promotes growth and induces the expression of its biosynthesis genes when iron is scarce. Growth promotion and signalling by pyochelin and enantio-pyochelin are highly stereospecific and are known to invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Iron uptake and signalling with E-Pch in P. fluorescens (b) is expected to proceed in a similar way, except that after FetA-dependent transport through the outer membrane, the iron-siderophore complex may cross the inner membrane via a classical ABC transport system encoded by genes of the fetABCDEF operon. Note that in the absence of FptA and FetA, respectively, activation of PchR by its cognate siderophore is reduced but not abolished (Youard and Reimmann 2010), implying that the siderophores can enter the cells also by an alternative, lowefficiency uptake pathway. Under iron-replete conditions, the Fur repressor blocks transcription of pchDCBA, pchR, pchEFGHI, and fptABCX in P. aeruginosa, and a similar repression of pchDHIEFKCBA, pchR, and fetABCDEF probably occurs in P. fluorescens (see text) Biometals (2011) 24:513-522 517 1994; Fig.…”
Section: Iron Uptakementioning
confidence: 97%
See 1 more Smart Citation
“…Iron uptake and signalling with E-Pch in P. fluorescens (b) is expected to proceed in a similar way, except that after FetA-dependent transport through the outer membrane, the iron-siderophore complex may cross the inner membrane via a classical ABC transport system encoded by genes of the fetABCDEF operon. Note that in the absence of FptA and FetA, respectively, activation of PchR by its cognate siderophore is reduced but not abolished (Youard and Reimmann 2010), implying that the siderophores can enter the cells also by an alternative, lowefficiency uptake pathway. Under iron-replete conditions, the Fur repressor blocks transcription of pchDCBA, pchR, pchEFGHI, and fptABCX in P. aeruginosa, and a similar repression of pchDHIEFKCBA, pchR, and fetABCDEF probably occurs in P. fluorescens (see text) Biometals (2011) 24:513-522 517 1994; Fig.…”
Section: Iron Uptakementioning
confidence: 97%
“…Interestingly, Pch and E-Pch are biologically active only in their producer species (Youard et al 2007;Hoegy et al 2009;Youard and Reimmann 2010), suggesting that iron uptake with these compounds is highly stereospecific.…”
Section: Introductionmentioning
confidence: 97%
“…All gene replacement mutants of P. aeruginosa and P. fluorescens listed in Table 1 were generated with suicide plasmids as described previously (Schnider et al, 1995;Ye et al, 1995;Laville et al, 1998). Apart from pME7152 (Michel et al, 2007), pME9253 (Youard & Reimmann, 2010) and pME9605 (Brillet et al, 2011), all new suicide plasmids were constructed in a similar way. First, two PCR fragments were generated from chromosomal DNA using primer pairs 1/2 and 3/4 (see Table S1 for nucleotide sequences).…”
Section: Methodsmentioning
confidence: 99%
“…Genetic, biochemical and structural data have so far revealed that stereospecificity of siderophore recognition occurs (i) at the outer membrane, by the receptors FptA and FetA (Hoegy et al, 2009;Brillet et al, 2011), and (ii) in the cytoplasm, by the two different versions of the regulatory proteins PchR, each of which is activated by its cognate siderophore only (Youard & Reimmann, 2010). The question of whether siderophore chirality is also important during transport across the inner membrane has not been addressed so far, mainly because the respective genes for ferriEPch transport in P. fluorescens have not been studied experimentally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation